Gender dan Feminisme dalam Perspektif Kamla Bhasin dan Leila Ahmed - Haitsam, Thoriq (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
This research examines what is actually the problem in incidents of sexual violence and gender inequality that have occurred in Hindu and Islamic societies. And what is the position of women in the views of the two religious feminist figures, namely Kamla Bhasin and Leila Ahmed. Based on these two things, the definition, causes and how to resolve the conflict that occurred will be elaborated on based on the thoughts of the two figures. This research uses a feminist and comparative approach, and also searches for library data, especially books containing the main thoughts of Kamla Bhasin and Leila Ahmed. Apart from that, researchers looked for other sources in the form of journals, theses, theses, articles, news, and results of interviews by bloggers/writers with these two figures through strict selection. In this study several findings were found: First, Islam and Hinduism basically glorify women. Teaching gender equality and justice, it's just that many people who act as interpreters of sacred texts and influential religious figures in society are misguided in interpreting and conveying their messages, this is due to the influence of cultural elements that are closely related to patriarchy. . Second, according to Kamla, many women are afraid to fight the patriarchy that restrains them because they are afraid of being accused of being against/opposing local religion and culture..